2019
DOI: 10.1016/j.cellimm.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular cancer-derived alpha fetoprotein uptake reduces CD1 molecules on monocyte-derived dendritic cells

Abstract: Alpha fetoprotein (AFP) is produced by over 50% of hepatocellular carcinomas (HCC). Uptake of tumor-derived AFP (tAFP) can impair activity of human dendritic cells (DC). The expression pattern of the lipid antigen presenting genes from the CD1 family is reduced in AFP-treated monocyte-derived DC. Surface CD1 family proteins, particularly CD1d, were reduced in AFP-exposed DC (by both normal cord blood-derived AFP (nAFP) and tAFP). NKT cells recognize lipid antigens presented by CD1d molecules. They play an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…In some cancers, full-length glycosylated AFP has immunosuppressive effects by stimulating cancer growth and directly activating MDSCs ( Pak, 2018a , b ). Moreover, tAFP significantly inhibits dendritic cell (DC) differentiation, thereby playing a critical role in immunosuppression ( Pardee et al, 2014 ; Li et al, 2019 ). Therefore, it is more suitable to use AIF than tAFP for manufacturing vaccines to prevent the initiation of cancer.…”
Section: Application Of Aif To Enhance Immunotherapy Of Cancermentioning
confidence: 99%
“…In some cancers, full-length glycosylated AFP has immunosuppressive effects by stimulating cancer growth and directly activating MDSCs ( Pak, 2018a , b ). Moreover, tAFP significantly inhibits dendritic cell (DC) differentiation, thereby playing a critical role in immunosuppression ( Pardee et al, 2014 ; Li et al, 2019 ). Therefore, it is more suitable to use AIF than tAFP for manufacturing vaccines to prevent the initiation of cancer.…”
Section: Application Of Aif To Enhance Immunotherapy Of Cancermentioning
confidence: 99%
“…NKT cells are also prominent in the microvasculature of the liver and play essential roles in normal physiology [65]. Given the prominence of NKTs in the liver and their emerging role in cancer immunotherapy [66], our group also sought to better understand how AFP might regulate CD1d molecules on DCs, thereby limiting NKT cell function in vitro [67]. We found that both nAFP and tAFP led to significant downregulation of CD1d on DCs; however, this did not diminish their potential to stimulate NKT cells [67].…”
Section: Box 3 Nkt Cell Dysregulation By Tafpmentioning
confidence: 99%
“…Given the prominence of NKTs in the liver and their emerging role in cancer immunotherapy [66], our group also sought to better understand how AFP might regulate CD1d molecules on DCs, thereby limiting NKT cell function in vitro [67]. We found that both nAFP and tAFP led to significant downregulation of CD1d on DCs; however, this did not diminish their potential to stimulate NKT cells [67]. Additional work is needed to fully understand the interplay between DCs and NKT cells, including the modulation of cytokines produced by NKT cells, focusing on a role for lipids in this cellular immune interaction.…”
Section: Box 3 Nkt Cell Dysregulation By Tafpmentioning
confidence: 99%
“…AFP can upregulate the expression of promoting apoptotic genes (such as Bax, Bid, Bad, etc. ), and induce apoptosis of immune cells (e.g., lymphocytes, dendritic cells) [93,94] . AFP can also upregulate the expression of proapoptotic factor genes in immuneinfiltrating cells in the tumor microenvironment.…”
Section: Resistance Of Hccmentioning
confidence: 99%